Development of Trade Relations between Kazakhstan and the Countries of Eurasian Economic Union (EAEU) - DOSMUKHAMEDOVA, Zarina; ZHIYENTAYEV, Sansyzbay (Journal of Advanced Research in Law and Economics; Vol 10 No 4 (2019): JARLE Vol X Issue 4(42) Summer 2019, 2019)
The purpose of research is to analyze strength of mutual trade relations between Kazakhstan and the EAEU countries. In addition, identification of the competitiveness of Kazakhstan export goods, in particular copper ore to the markets of the EAEU countries. To achieve the identified research goal, we examine the theoretical and practical integration issues. The results show that as long as the Trade Union is established, the share of mutual trade and investment has increased. However, the remaining unresolved issues impede the implementation of the Union’s goal, that is freedom of goods, services, finance and labor mobility. The authors highlight and describe the characteristic features that have contributed to the EAEU establishment. It has been brought to the sharp focus that the EAEU competition is intensifying in the current context to ensure the objective basis for considering Public Regulation of Agricultural Sector. Along, this research, the author used methodological approaches to underline the changes of integration processes: analysis of mutual relations and sectoral analysis as well as approaches of scientific abstraction, comparative analysis and a retrospective analysis of integration processes that had been carried out. To make analysis of Kazakhstan's trade relations with the EAEU countries, the author implemented various approaches. In particular, materialist dialectics, the rising from the abstract to the concrete, induction and deduction, comparative analysis, and other approaches that made it possible to analyze the development of the trade relations between Kazakhstan and the said countries were implemented. These approaches enhanced identification of the strengths and weaknesses of the trade development in Kazakhstan and explored the dynamics of mutual flows either investments or goods.The conclusion contains some summarizing notes addressed to strengthening of economic ties within the Union.